Nicola Hicks - keep dark - Mamet, David 1947-; McWilliam, Candia 1955-; Porter, Max 1981-; Pye, Matilda; Self, Will 1961-; Sims, Patterson (Elephant, 2017)
"Nicola Hicks's sculpture and drawing practice has focused upon heroic, humanized animals and mythic, beast-like humans. From the moment she burst upon the wider public stage, there has been no doubting her remarkable talent. Picked out while still at the Royal College of Art by the late Elisabeth Frink as a fellow spirit, she quickly established an immediate presence among the artists of her generation as a serious and substantial figure. She was remarkable on every count, for she flew in the face of the critical expectations of those days not just in the nature of the actual imagery she celebrated--figurative, romantic and expressive--but also in the direct and gleeful joy she took in the physical making of these things. This book is a visual celebration of her work and features essays written by Will Self, Max Porter, Candia McWilliam and David Mamet."--Amazon.com
Keywords: Hicks, Nicola -- 1960-; Hicks, Nicola / 1960- / Criticism and interpretation; Hicks, Nicola / 1960-; Sculpture, English / 20th century; Sculpture, English / 21st century; Drawing, English / 20th century; Drawing, English / 21st century; Animals in art; Drawing, English; Sculpture, English; 1900-2099; Criticism, interpretation, etc; Bildband